Improving Regional Potential in the Field of Sports Through Volleyball Matches in Panulisan Village, Cilacap Regency - Dias Galih Dwipangestu; Hikmah Maulid Rahman; Hengki Kurniawan; Rikha Surtika Dewi; Maesaroh Lubis (Indo Publishing, 2025)
The purpose of this research is because there is information or reports that there are many hidden talents in Panulisan village, especially in the field of volleyball sports which are mostly favored by early childhood, Sports are physical activities in the form of games that contain struggles against natural elements, other people or oneself which are carried out regularly and in a planned manner to improve their functional abilities. Of course, every region has potential in the field of sports. One of them is the potential of Panulisan village, namely in volleyball. This is in accordance with the results of observations of the potential of Panulisan village. According to community leaders, most residents of Panulisan village have skills in playing volleyball. Even the ancestors of Panulisan village were also experts in playing volleyball. Therefore, a volleyball tournament for the boys category between Elementary Schools was held in Panulisan village with the hope that it could be a provision, experience, and help develop potential, especially in the field of volleyball.